Hypericin, a potential new BH3 mimetic - Doroshenko, Anastasia; Tomkova, Silvia; Kozar, Tibor; Stroffekova, Katarina (Frontiers in Pharmacology, 2022)
Many types of cancer such as prostate cancer, myeloid leukemia, breast cancer, glioblastoma display strong chemo resistance, which is supported by enhanced expression of multiple anti-apoptotic Bcl-2, Bcl-XL and Mcl-1 proteins. The viable anti-cancer strategies are based on developing anti-apoptotic Bcl-2 proteins inhibitors, BH3 mimetics. Our focus in past years has been on the investigating a new potential BH3 mimetic, Hypericin (Hyp). Hyp is a naturally occurring photosensitive compound used in photodynamic therapy and diagnosis. We have demonstrated that Hyp can cause substantial effects in cellular ultrastructure, mitochondria function and metabolism, and distribution of Bcl2 proteins in malignant and non-malignant cells. One of the possible mechanisms of Hyp action could be the direct interactions between Bcl-2 proteins and Hyp. We investigated this assumption by in silico computer modelling and in vitro fluorescent spectroscopy experiments with the small Bcl2 peptide segments designed to correspond to Bcl2 BH3 and BH1 domains. We show here that Hyp interacts with BH3 and BH1 peptides in concentration dependent manner, and shows the stronger interactions than known BH3 mimetics, Gossypol (Goss) and ABT-263. In addition, interactions of Hyp, Goss and ABT263, with whole purified proteins Bcl-2 and Mcl-1 by fluorescence spectroscopy show that Hyp interacts stronger with the Bcl-2 and less with Mcl-1 protein than Goss or ABT-263. This suggest that Hyp is comparable to other BH3 mimetics and could be explore as such. Hyp cytotoxicity was low in human U87 MG glioma, similar to that of ABT263, where Goss exerted sufficient cytotoxicity, suggesting that Hyp acts primarily on Bcl-2, but not on Mcl-1 protein. In combination therapy, low doses of Hyp with Goss effectively decreased U87 MG viability, suggesting a possible synergy effect. Overall, we can conclude that Hyp as BH3 mimetic acts primarily on Bcl-2 protein and can be explored to target cells with Bcl-2 over-expression, or in combination with other BH3 mimetics, that target Mcl-1 or Bcl-XL proteins, in dual therapy.